The Ethnobotany and Ethnomedicine of Zanthoxylum acanthopodium in Lake Toba, North Sumatra, Indonesia - Cut Rizlani Kholibrina; Aswandi Aswandi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Zanthoxylum acanthopodium is a nutritional plant utilized for both culinary and medicinal purposes. The herb, popularly known as andalimanis found in sloppy, barren, cultivated lands and secondary forests in Lake Toba, North Sumatra. This study aimed to provide an ethnobotanical description, productivity and propagation, essential oil of andaliman and the application as traditional medicine in Lake Toba. Botanical characters were collected by observing phenology and distilling essential oils. The ethnomedicine information was collected through in-depth interviews with farmers and herbal practitioners, meanwhile, phytochemical content was identified based on various primary literature. Results showed flowering period occurs from March until April and followed by fruiting in May to September. Fruits were widely processed as cooking spices for various cuisines. It played an important role in local people’s diet by supplying carbohydrate, minerals and vitamins. This ingredient was favoured for its citrus-colored oil content and a spicy taste with an appetizing aroma. This spice was also utilized in traditional medicine. Both dry and fresh fruits were used for gums and dental disorders as dyspepsia or lotion for scabies. Fresh roots were also used to cure dental problems. All plant plants contain essential oil with a higher concentration in fruits (4.89%). The local wisdom also reveals the essential oil utilization as an antimicrobial ingredient that could be further processed as a food preservative. To increase generative propagation, seed dormancy breaking treatment through a low-intensity burning can increase the germination rate.